Applied ecological research is on the rise but connectivity barriers persist between four major subfields. Issue 6 (13th March 2019) - Staples, Timothy L.; Dwyer, John M.; Wainwright, Claire E.; Mayfield, Margaret M.
Abstract: Climate change, land clearing and invasive species are affecting ecosystems in concert, so effective management requires knowledge sharing and collaboration across multiple fields of applied ecological research. We provide an examination of the growth and interconnectivity of four major subfields of applied ecology: climate change biology, conservation biology, invasion biology and restoration ecology; estimated using citations from the entire population of peer‐reviewed journal articles published between 1990 and 2017. Over this period applied ecological research has grown from 2% of new ecology papers to over 20%. The subfields each represented c . 6% of new ecology publications in 2017, with the exception of restoration ecology at c . 3%. Inter‐subfield citation probabilities also increased consistently over our study period. Despite these positive trends, we identified apparent barriers to future integration of these research areas. While the probability that citations in one subfield would include at least one paper from another subfield was high, the magnitude of cross‐subfield citations was low. Subfields also exhibited segregated publishing habits, asynchronous research foci and a strong preference for citing application over theory. Synthesis and applications . Despite strong overall growth in applied ecological research, segregation of subfields in papers and journals may limit opportunities to identify co‐benefits and complementary theoretical frameworks. This has the potential to result in suboptimal ecological management outcomes. Abstract : Despite strong overall growth in applied ecological research, segregation of subfields in papers and journals may limit opportunities to identify co‐benefits and complementary theoretical frameworks. This has the potential to result in suboptimal ecological management outcomes.